1980
DOI: 10.1104/pp.66.5.793
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Endogenous Gibberellin-like Substances with Sex Reversal of the Apical Inflorescence of Corn

Abstract: In developing apical meristems of corn, the level of acidic, ethyl acetate-soluble gibbereilin (GA)-ike substances increased to a maximum of 108 micrograms GA3requivalents per kilogram dry weight of tissue at inflorescence initiation, and then fel rapidly. At anthesis, only a trace (0.2 microgram per kilogram) of GA-like activity remained in the apical (male) inflorescences, whereas moderate activity (32 micrograms per kilogram), mostly of a nonpolar nature, was present in lateral, female, inflorescences.A sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 19 publications
5
32
1
Order By: Relevance
“…Although the mechanism is unknown, this result together with the genetic evidence invites the notion that high level of GA in specific cells suppresses cell growth and differentiation; whereas low level of GA promotes cell growth and differentiation. This notion is supported by the evidences: 1) the level of GA in the tassel is much lower than in the ear; 10 2) application of GA converts male florets to female florets in the tassel. 11 Thus, we postulate that high level of bioactive GA suppresses the stamen development in tassel florets.…”
Section: Ga Can Be Synthesized In the Nucleus And Cytosolsupporting
confidence: 70%
“…Although the mechanism is unknown, this result together with the genetic evidence invites the notion that high level of GA in specific cells suppresses cell growth and differentiation; whereas low level of GA promotes cell growth and differentiation. This notion is supported by the evidences: 1) the level of GA in the tassel is much lower than in the ear; 10 2) application of GA converts male florets to female florets in the tassel. 11 Thus, we postulate that high level of bioactive GA suppresses the stamen development in tassel florets.…”
Section: Ga Can Be Synthesized In the Nucleus And Cytosolsupporting
confidence: 70%
“…At least two possibilities offer an explanation for this phenomenon: first, GA does not affect the stamen primordium development in male floret; or second, the level of GAs in the tassel is too low to induce the suppression of stamen primordia. A previous study reported that the amount of GA-like substances in the tassel was much lower than in the ear (Rood and Pharis, 1980). Consistently, no strong signal was detected by immunohistochemical analysis with D1 antibody in tassel florets (Fig.…”
Section: The Suppression Of Stamen Primordia In Maize Female Florets supporting
confidence: 51%
“…The determination of the sex expression may thus be regulated by other factors than cytokinins alone. Feminizing effects have also been reported for auxins and abscisic acid (5,6,24) and for gibberellins (3,5,13,22,25).…”
Section: Discussionmentioning
confidence: 91%